Archaeologies of Early Modern Spanish Colonialism - Montón-Subías, Sandra; Cruz Berrocal, María; Ruiz Martínez, Apen (Contributions To Global Historical Archaeology, 2016)
XII, 302 p. 83 illus., 31 illus. in color.